Distribution and Ethnomedicinal Importance of Orchids of Darjeeling Himalaya, India - Rahamtulla, Mohammed; Rampilla, Venkatesh; Khasim, Shaik Mahammad (Indian Forester, 2020)
The present study highlights the distribution and ethnobotanical aspects of orchids distributed in forests, grasslands and some tribal hamlets from Darjeeling Himalaya (West Bengal). Extensive field surveys have been undertaken during 2019-2020. Ethnomedicinal data was collected with indepth questioner from 15 key informants of Bhutia tribe and some rural inhabitants of Darjeeling Himalaya. Data was analyzed and fidelity level (FL) calculated for all orchids. An analysis of data indicates that 8 species (67%) were epiphytic and 4 species (33%) were terrestrial, apart from this altitudinal variation is also recorded. The orchids such as Eria flava and Dendrobium transparens were recorded at the lowest (234 m) and the highest (1662 m) altitudes respectively Out of 12 species, Paphiopedilum venustum is an endganered (EN) orchid where as Bulbophyllum leopardinum, Dendrobium aphyllum and Vanda tessellata are least concern (LC) species as per lUCN Red List of threatened species Version 2019-3. All these orchids used to cure various ailments, for example, Coelogyne ochracea has been referred to bone fractures and Dendrobium aphyllum to snakebites. Therefore, the present study strongly recommends the habitat monitoring and conducting awareness programs for the local inhabitants for conserving this exceptional group of plants because Darjeeling hill region is congenial for luxuriant growth of orchids.